Challenges In Developing A Digital Educational Environment - Abdulxakimov Zuhrali Tursunalievich; Abdul Rahmat (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The article discusses the factors that effectively shape the digital learning environment. In addition, the article details the need for the digital learning environment of the education system to be a single communication space for all participants in educational relations, an effective tool for managing the quality of educational programs, teacher performance.